Insect biodiversity : science and society - Adler, Peter H. [ (Peter Holdridge)] , 1954-; Foottit, R. [ (Robert G.)] (Wiley-Blackwell, 2009)
Insect Biodiversity: Science and Society brings together leading scientific experts to assess the impact insects have on humankind and the earth's fragile ecosystems. It examines why insect biodiversity matters and how the rapid evolution of insect species is affecting us all